2016
DOI: 10.1007/s11999-016-4828-x
|View full text |Cite
|
Sign up to set email alerts
|

What Provisions Do Orthopaedic Programs Make for Maternity, Paternity, and Adoption Leave?

Abstract: Background The process of choosing medical specialty and residency programs is multifaceted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 5 publications
2
46
0
1
Order By: Relevance
“…As such, when one member is down, everyone else needs to step up. Resentment can build among the residents left to shoulder the burden when a member of the team becomes pregnant [5] However, there were some uncomfortable choices. In 1996, we had a different understanding and prognosis for human immunodeficiency virus (HIV)/AIDS.…”
Section: A Tale Of Two Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, when one member is down, everyone else needs to step up. Resentment can build among the residents left to shoulder the burden when a member of the team becomes pregnant [5] However, there were some uncomfortable choices. In 1996, we had a different understanding and prognosis for human immunodeficiency virus (HIV)/AIDS.…”
Section: A Tale Of Two Familiesmentioning
confidence: 99%
“…Recognizing the values and prejudices which make pregnancy a challenging experience for orthopaedic surgeons offers a starting point for solutions. A recent survey of orthopaedic training programs [5] demonstrated a modest number offering formal paternity and adoption leave. Despite a federal Family Medical Leave Act, which provides for 12 weeks of maternity leave, a 2012 study [3] showed an average of 4 weeks for residents or fellows.…”
Section: Maternity Leavementioning
confidence: 99%
“…5 Residency faculty are role models and mentors as residents make decisions about career paths and practice locations, and the environment where women train strongly influences these choices. [6][7][8][9] Creating policies that allow women ORIGINAL ARTICLES faculty to succeed is essential for meeting the ongoing need for teaching faculty who will develop the future physician workforce. 10 Leave policies for nonchildbearing parents are also important.…”
mentioning
confidence: 99%
“…[11][12][13][14] Despite this, leave policies vary greatly across programs and disciplines. 8,[15][16][17][18] A 2016 survey of surgery residency programs showed less than half of programs had a paternity leave policy and, when present, paternity leave was typically 1 week. 2 Pediatric program directors reported 61% had policies for paternity leave and approximately one-third had policies for domestic partnerships or same-gender unions.…”
mentioning
confidence: 99%
See 1 more Smart Citation